Studying hazard perception in driving at the laboratory: a review - Amaro Egea-Caparrós, Damián (Anales de Psicología / Annals of Psychology, 2012)
This paper analyzes thirty experimental studies on hazard perception in traffic, all of them made in the laboratory. We present the results of this review about the way of showing the stimuli –traffic situations in which a hazard is involved-, that is, video and driving simulation, the degree of realism –through the use of sound in the video clips and the size of the screen, the definition of hazard given to the participants and the variables of hazard detection used. Moreover, other methodological aspects are discussed: the concern about separating age and driving experience, and the use of control variables. In the discussion of the main results we point that most of the studies use video presentation of real traffic scenes but almost all of them have no sound, which supposed effect has not been systematically studied yet. Be- sides, enlarging the field of view yield the speeding of latency or response time to hazard. This variable is capable of discriminate among novice and experienced drivers. Finally, it is possible to train this ability in drivers with different age and driving experience.